2017
DOI: 10.1530/eje-16-0779
|View full text |Cite
|
Sign up to set email alerts
|

Affective alterations in patients with Cushing’s syndrome in remission are associated with decreased BDNF and cortisone levels

Abstract: Low BDNF levels are associated with affective alterations in 'cured' CS patients, including depression, anxiety and impaired stress perception. Elevated levels of SalE might also be related to poor affective status in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…PIT-CS found a total CushingQoL score of 40 ± 10 and 50 ± 18, after 6 and 16 years of remission, respectively. 16,18 Of note, Wagenmakers et al showed that better CushingQoL scoring is associated with longer duration of remission, consistent with previous observations reporting a gradual improvement in psychopathology after correction of cortisol excess. 4 On the contrary, and in agreement with other studies, we did not find an association between HRQoL scores and duration of remission, likely because remission had occurred a long time before in most patients.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…PIT-CS found a total CushingQoL score of 40 ± 10 and 50 ± 18, after 6 and 16 years of remission, respectively. 16,18 Of note, Wagenmakers et al showed that better CushingQoL scoring is associated with longer duration of remission, consistent with previous observations reporting a gradual improvement in psychopathology after correction of cortisol excess. 4 On the contrary, and in agreement with other studies, we did not find an association between HRQoL scores and duration of remission, likely because remission had occurred a long time before in most patients.…”
Section: Discussionsupporting
confidence: 74%
“…In particular, the total CushingQoL score was 60 ± 19 in PIT‐CS and 63 ± 23 in ADR‐CS, with similar scores on all the specific items of CushingQoL. Previous studies using the CushingQoL questionnaire to evaluate HRQoL in long‐term “cured” PIT‐CS found a total CushingQoL score of 40 ± 10 and 50 ± 18, after 6 and 16 years of remission, respectively …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Predictors for postoperative improvement in QoL were greater preoperative QoL impairment and a younger age, as also reported using the CushingQoL questionnaire (60). Other predictors of impaired QoL are having experienced a long delay until a correct diagnosis of CS was obtained (61) or having seen more physicians before a correct diagnosis of CS was made (62,63). Whether this means that patients who experience greater discomfort demand more physician visits or it simply indicates a longer duration of symptoms is not yet clear.…”
Section: Cushing's Diseasementioning
confidence: 62%
“…Some other studies 6,8,9,14 found increased levels of BDNF in the primary afferent neurons of the dorsal root ganglia in animal models of colitis and the same was shown in patients with irritable bowel syndrome (IBS). 15,18,19 Nevertheless, contrary to what was initially believed, stress may induce an increase in the expression of BDNF levels 20 as a coping mechanism to protect neuronal function and plasticity. 15,16 It is surprising that in the present study, serum BDNF concentrations were higher in patients on GFD than in the untreated ones, even though GFD eliminates small bowel inflammation 17 and we have no apparent explanation for this at this time.…”
Section: Discussionmentioning
confidence: 92%